A method for detecting the polishing quality of a nickel mesh substrate

CN122671516BActive Publication Date: 2026-10-23QINGQIJI ZHONGNENG (SUZHOU JIANGSU) HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611184000.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-23
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

[0004]为此,本发明所要解决的技术问题在于克服现有技术中对镍网基底打磨质量的检测需离线取样、依赖大型仪器或人工主观判断,无法同时定量评价去氧化层效果和增粗糙效果且难以实现在线快速反馈的不足,提供一种镍网基底的打磨质量检测方法,利用电化学阻抗谱同时提取反映表面粗糙度的特征频率参量和反映氧化层残留程度的阻抗比值参量,通过双重判定标准综合评价打磨质量,并可根据偏离状态实施差异化的工艺反馈调节,无需制样、不破坏基底、可在线快速检测

Benefits of technology

本发明所述的镍网基底的打磨质量检测方法,通过将打磨后的镍网基底构建为三电极检测体系,并利用电化学阻抗谱技术提取特征频率和Rct/Rs比值作为打磨质量的判定依据,实现了对镍网基底打磨质量的快速、无损、定量化检测。该方法能够有效评估镍网表面氧化层去除程度和表面粗糙度,克服了现有技术中离线检测耗时、主观性强、无法在线全检的局限,并能根据检测结果及时反馈并调节打磨工艺参数,从而提高了生产效率和产品质量的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122671516B_ABST
    Figure CN122671516B_ABST
Patent Text Reader

Abstract

The application discloses a kind of nickel mesh substrate polishing quality detection method, suitable for nickel mesh substrate is twill weave nickel mesh, comprising the following steps: after polishing, nickel mesh substrate is immersed in alkaline electrolyte, to constitute three-electrode system with it as working electrode;Apply alternating current disturbance signal, carry out electrochemical impedance spectroscopy scanning under 10mHz-100kHz frequency range and open circuit potential;From impedance spectrogram, the maximum value corresponding to characteristic frequency in the phase angle of 10Hz-1kHz intermediate frequency band is extracted, and the ratio Rct / Rs of charge transfer resistance Rct and solution resistance Rs;When characteristic frequency enters preset target frequency band and Rct / Rs is not lower than preset lower limit value, it is judged to be qualified, otherwise unqualified;When unqualified, adjust polishing process parameters according to deviation state.The application can evaluate the deoxidation layer effect and roughening effect of polishing simultaneously, realize no need to sample, do not destroy substrate, can be on-line rapid detection and closed-loop feedback.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nickel mesh polishing and testing technology, and in particular to a method for testing the polishing quality of a nickel mesh substrate. Background Technology

[0002] Nickel mesh, as a metal braided material with good conductivity, corrosion resistance, and structural stability, is used in various industrial fields as a filter element, shielding material, or electrode substrate. Its surface condition directly affects subsequent processing and performance. Among the many processing steps for nickel mesh, grinding pretreatment is a common and crucial step. Its purpose is to remove the oxide layer and adhering impurities naturally formed on the surface of the nickel mesh during preparation or storage, while simultaneously creating a certain degree of microscopic roughness through mechanical action. The quality of grinding directly affects the adhesion and bonding strength of subsequent processes such as coating, welding, or electrochemical deposition, ultimately impacting the reliability and service life of the finished product. Therefore, effective monitoring of grinding quality is essential during the production process.

[0003] In existing technologies, the inspection of the grinding quality of nickel mesh substrates mainly involves offline sampling followed by surface morphology observation using optical microscopes, scanning electron microscopes, or atomic force microscopes. Surface roughness parameters or energy dispersive spectroscopy (EDS) data are then used to determine whether the oxide layer has been completely removed. However, these methods typically require removing samples from the production line and placing them in a dedicated equipment chamber for testing. This process is cumbersome, time-consuming, and the test results cannot be promptly fed back to the grinding process, making it difficult to achieve full online inspection of every batch of products. Some production sites also use simple methods such as manual visual observation or tape peeling, relying on changes in surface color or the presence of oxide scale debris on the tape to qualitatively judge the grinding effect. However, these methods are highly subjective, lack quantitative standards, and cannot simultaneously assess the degree of oxide layer removal and whether the surface roughness meets the anchoring requirements of subsequent processes. Therefore, there is an urgent need for a rapid, non-destructive, and online quantitative inspection method for the grinding quality of twill braided nickel mesh substrates. Summary of the Invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the shortcomings of the existing technology for detecting the grinding quality of nickel mesh substrates, which requires offline sampling, relies on large instruments or subjective human judgment, cannot simultaneously quantitatively evaluate the oxide layer removal effect and roughening effect, and is difficult to achieve online rapid feedback. The present invention provides a method for detecting the grinding quality of nickel mesh substrates, which uses electrochemical impedance spectroscopy to simultaneously extract characteristic frequency parameters reflecting surface roughness and impedance ratio parameters reflecting the degree of oxide layer residue. The grinding quality is comprehensively evaluated through dual judgment criteria, and differentiated process feedback adjustment can be implemented according to the deviation state. It does not require sample preparation, does not damage the substrate, and can be detected online rapidly.

[0005] To address the aforementioned technical problems, this invention provides a method for inspecting the polishing quality of a nickel mesh substrate, wherein the nickel mesh substrate is a twill-woven nickel mesh, and includes the following steps: The polished nickel mesh substrate is immersed in an alkaline electrolyte, and the nickel mesh substrate is used as the working electrode, together with the reference electrode and the counter electrode, to form a three-electrode detection system. An AC perturbation signal was applied to the working electrode using an electrochemical workstation, and an electrochemical impedance spectroscopy scan was performed in the frequency range of 10 mHz to 100 kHz. The impedance spectrum was recorded. The electrochemical impedance spectroscopy scan was performed at the open circuit potential of the nickel mesh substrate. The following characteristic parameters are extracted from the impedance spectrum: the maximum value of the phase angle in the mid-frequency band of 10Hz to 1kHz and its corresponding characteristic frequency, and the ratio of charge transfer resistance Rct to solution resistance Rs, Rct / Rs. When the characteristic frequency enters the preset target frequency band and the Rct / Rs ratio is not lower than the preset lower limit, the polishing quality is deemed to be qualified; otherwise, the polishing quality is deemed to be unqualified. The preset target frequency band is the characteristic frequency range that indicates that the surface roughness of the nickel mesh after polishing has reached the required level. The preset lower limit is the critical Rct / Rs value that indicates that the oxide layer on the surface of the nickel mesh has been removed after polishing. When the grinding quality is deemed unqualified, the grinding process parameters are adjusted based on the deviation of the characteristic frequency from the preset target frequency band and the deviation of the Rct / Rs ratio from the preset lower limit.

[0006] In one embodiment of the present invention, the alkaline electrolyte is an aqueous solution of potassium hydroxide, and the concentration of the aqueous solution of potassium hydroxide is 0.5 mol / L to 6 mol / L.

[0007] In one embodiment of the present invention, the reference electrode is a saturated calomel electrode or a silver / silver chloride electrode, and the counter electrode is a platinum sheet electrode or a platinum mesh electrode.

[0008] In one embodiment of the present invention, the amplitude of the AC disturbance signal is 5 to 10 mV.

[0009] In one embodiment of the present invention, the open circuit potential is determined by placing the working electrode, reference electrode and counter electrode in the three-electrode detection system into an alkaline electrolyte. When the potential value of the working electrode after contact with the alkaline electrolyte fluctuates by no more than ±1mV within 5 minutes, the stable potential value is taken as the open circuit potential.

[0010] In one embodiment of the present invention, the maximum value of the phase angle in the mid-frequency band of 10Hz to 1kHz and its corresponding characteristic frequency are extracted in the following manner: Plot the phase angle-frequency curve with the phase angle as the vertical axis and the logarithm of the frequency as the horizontal axis from the impedance spectrum. Determine the maximum point of the phase angle in the frequency range of 10Hz to 1kHz, and use the frequency value corresponding to the maximum point as the characteristic frequency. Specifically: if multiple phase angle maxima exist within the frequency range of 10Hz to 1kHz, the frequency value corresponding to the largest maximum value is selected as the characteristic frequency; if no clear phase angle maxima peak appears within the frequency range of 10Hz to 1kHz, the polishing quality of the nickel mesh substrate is deemed unqualified.

[0011] In one embodiment of the present invention, the ratio Rct / Rs of the charge transfer resistance Rct to the solution resistance Rs is extracted in the following manner: Plot the Nyquist plot with the real impedance Z′ on the horizontal axis and the imaginary impedance -Z″ on the vertical axis. The impedance value corresponding to the intersection of the high-frequency arc and the real impedance axis in the Nyquist plot is the solution resistance Rs. The difference between the impedance value corresponding to the intersection of the low-frequency arc and the real impedance axis in the Nyquist plot and Rs is the charge transfer resistance Rct.

[0012] In one embodiment of the present invention, the preset target frequency band is calibrated through the following steps: Take at least three fully polished nickel mesh standard samples and at least three unpolished nickel mesh samples. The fully polished nickel mesh standard samples are nickel meshes whose surface oxide layer has been removed and whose surface roughness Ra reaches 1.5μm to 3.0μm as confirmed by scanning electron microscopy. The unpolished nickel mesh samples are twill woven nickel meshes from the same batch that have not undergone any polishing treatment. Electrochemical impedance spectroscopy was performed on each nickel mesh standard sample and the unpolished sample under the same test conditions, and the phase angle-frequency curves of each sample were recorded. The characteristic frequency values ​​corresponding to the maximum values ​​of the phase angle in the mid-frequency band of 10Hz to 1kHz for each nickel mesh standard sample and unpolished sample were extracted respectively, and the arithmetic mean of the characteristic frequencies of the two groups of samples was calculated respectively. The lower limit of the target frequency band is determined by adding one standard deviation to the upper limit of the arithmetic mean of the characteristic frequencies of the unpolished sample group, and the upper limit of the target frequency band is determined by subtracting one standard deviation from the lower limit of the arithmetic mean of the characteristic frequencies of the nickel mesh standard sample group.

[0013] In one embodiment of the present invention, the preset lower limit value is calibrated through the following steps: Take at least three fully polished nickel mesh standard samples. The fully polished nickel mesh standard samples are nickel meshes that, under the same polishing conditions, have a uniform silvery-white metallic luster when visually inspected and have a surface oxygen atomic percentage of less than 1% confirmed by scanning electron microscopy energy dispersive spectroscopy analysis. Each nickel mesh standard sample was tested under electrochemical impedance spectroscopy scanning conditions. The Rct / Rs value of each nickel mesh standard sample was calculated and the arithmetic mean was taken. The value obtained by subtracting three times the standard deviation from the arithmetic mean was used as the preset lower limit value.

[0014] In one embodiment of the present invention, adjusting the polishing process parameters includes: When the characteristic frequency is lower than the preset target frequency band, increase the grinding mesh of the quartz sand; When the characteristic frequency is higher than the preset target frequency band, reduce the grinding mesh of the quartz sand; When the characteristic frequency falls into the preset target frequency band, but the Rct / Rs ratio is lower than the preset lower limit, the current quartz sand grinding mesh is maintained. The grinding time is extended, and a surface cleaning process is added after grinding.

[0015] The technical solution of the present invention has the following advantages compared with the prior art: The present invention describes a method for detecting the grinding quality of nickel mesh substrates. This method constructs a three-electrode detection system on the ground nickel mesh substrate and utilizes electrochemical impedance spectroscopy to extract characteristic frequencies and the Rct / Rs ratio as criteria for judging grinding quality. This achieves rapid, non-destructive, and quantitative detection of the grinding quality of the nickel mesh substrate. This method can effectively assess the degree of oxide layer removal and surface roughness of the nickel mesh surface, overcoming the limitations of existing technologies such as time-consuming offline detection, strong subjectivity, and inability to perform full online inspection. Furthermore, it can provide timely feedback and adjust grinding process parameters based on the detection results, thereby improving production efficiency and product quality stability. Attached Figure Description

[0016] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein: Figure 1 This is a flowchart of the steps in the method for detecting the polishing quality of the nickel mesh substrate of the present invention; Figure 2 This is a phase angle-frequency curve plotted by monitoring a nickel mesh substrate according to the present invention; Figure 3 This is a Nyquist plot generated by monitoring a nickel mesh substrate according to the present invention. Detailed Implementation

[0017] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0018] Reference Figure 1As shown, this invention provides a method for detecting the polishing quality of nickel mesh substrates. Utilizing the highly sensitive nature of electrochemical impedance spectroscopy to the state of the electrode interface, the polished nickel mesh substrate is directly used as the working electrode. Together with the reference electrode and the counter electrode, they form a three-electrode detection system immersed in an alkaline electrolyte. By applying a small-amplitude AC perturbation signal at an open-circuit potential, a wide-band impedance spectrum scan is performed. Two key characteristic parameters are extracted from the obtained impedance spectrum: the characteristic frequency corresponding to the maximum phase angle in the mid-frequency band and the ratio of charge transfer resistance to solution resistance—serving as evaluation indicators of polishing quality.

[0019] It is well known in the art that electrochemical impedance spectroscopy can reflect the electrochemical information of the electrode / electrolyte interface. However, in conventional applications, impedance spectroscopy is mostly used to study the protective performance or corrosion behavior of coatings. Using impedance spectroscopy to detect the grinding quality of metal substrates is not an obvious approach. The inventive concept of this application stems from a deep understanding of the essence of the grinding process: the grinding process has two core objectives, one is to remove the surface oxide layer through mechanical grinding, and the other is to form a specific microstructure by abrasive grains traversing the surface. The former changes the chemical composition and conductivity of the surface, while the latter changes the surface geometry and actual area. The presence of an oxide layer is equivalent to covering the metal substrate surface with an insulating film, which significantly hinders the transfer of interfacial charges; while changes in surface roughness affect the capacitive behavior of the interfacial double layer, because the actual area of ​​a rough surface is larger than its apparent area, and roughness also determines the frequency response characteristics of the electrode interface. It is precisely based on the distinction between these two physical processes that it is possible to devise a technical approach to evaluate the deoxide layer effect and the roughening effect separately using electrochemical methods, and then choose electrochemical impedance spectroscopy as the detection tool, because impedance spectroscopy can distinguish the capacitance response and charge transfer response of the interface at different frequencies.

[0020] Based on the above concept, this application uses the polished nickel mesh substrate as the working electrode and immerses it in an alkaline electrolyte to construct a three-electrode system for impedance spectroscopy testing.

[0021] In this embodiment, the alkaline electrolyte is an aqueous solution of potassium hydroxide, with a concentration of 0.5 mol / L to 6 mol / L. Potassium hydroxide (KOH) aqueous solution, as an alkaline electrolyte, possesses excellent ionic conductivity, ensuring efficient charge transport during electrochemical impedance spectroscopy scanning. Nickel undergoes specific electrochemical reactions in an alkaline environment, and the formation and dissolution of its surface oxide layer (e.g., Ni(OH)2, NiOOH, etc.) are closely related to the polishing quality of the nickel mesh substrate. The selection of potassium hydroxide aqueous solution aims to provide a stable alkaline electrochemical environment for the nickel mesh substrate, which is crucial for accurately capturing and reflecting the electrochemical response of the nickel mesh substrate surface state, thereby effectively improving the sensitivity and accuracy of the detection method. Furthermore, the chemical properties of potassium hydroxide aqueous solution are relatively stable, and it is not prone to decomposition or interfering side reactions during detection, contributing to the long-term stable operation of the entire detection system. The concentration of the potassium hydroxide aqueous solution is limited to the range of 0.5 mol / L to 6 mol / L because the concentration of the electrolyte is a key factor affecting its conductivity, pH value, and electrochemical reaction kinetics on the nickel mesh substrate surface. When the concentration of the potassium hydroxide aqueous solution is below 0.5 mol / L, the ionic conductivity of the electrolyte may be insufficient, resulting in an excessively high solution resistance Rs, which in turn affects the measurement accuracy of impedance spectroscopy data and may not provide enough hydroxide ions to stabilize the redox reaction on the nickel mesh substrate surface. Conversely, when the concentration is above 6 mol / L, although the conductivity of the electrolyte may be further enhanced, the excessively high concentration may lead to a significant increase in solution viscosity, thereby limiting the ion diffusion rate. It may also cause excessive corrosion or passivation effects on the nickel mesh substrate surface, which may mask subtle electrochemical changes caused by differences in polishing quality and even affect the long-term stability of the working electrode. Therefore, the concentration of potassium hydroxide aqueous solution is precisely controlled within the range of 0.5 mol / L to 6 mol / L in order to optimize the overall performance of the electrolyte and ensure that the electrochemical impedance changes on the nickel mesh substrate surface caused by the difference in polishing quality can be clearly and accurately detected under the premise that the electrochemical reaction proceeds stably.

[0022] Specifically, the reference electrode was selected as a saturated calomel electrode or a silver / silver chloride electrode, and the counter electrode was selected as a platinum sheet electrode or a platinum mesh electrode. The reference electrode plays a crucial role in electrochemical measurements by providing a stable potential reference point; its potential stability and repeatability directly affect the accuracy of the working electrode potential measurement. The saturated calomel electrode is a reference electrode composed of mercury, mercurous chloride (calomel), and a saturated potassium chloride solution. It exhibits stable potential and good reproducibility, providing a reliable reference potential in aqueous systems. The silver / silver chloride electrode consists of a silver wire coated with a silver chloride layer and immersed in an electrolyte containing chloride ions. It possesses good potential stability, temperature adaptability, and a low liquid junction potential, making it particularly suitable for alkaline systems. Both of these reference electrodes are widely recognized for their excellent electrochemical performance.

[0023] Meanwhile, the counter electrode, also known as the auxiliary electrode, primarily functions to provide a current loop to balance the electrochemical reactions occurring on the working electrode. The counter electrode should have a sufficiently large surface area to ensure a fast enough electrochemical reaction rate, avoiding becoming a current limiting factor, and should remain inert during the reaction to prevent contamination of the electrolyte or working electrode. Platinum sheet electrodes, made of pure platinum metal, possess excellent conductivity, chemical inertness, and electrocatalytic activity. Their large surface area allows them to withstand high current densities and they are not easily corroded in various electrolytes. Platinum mesh electrodes, woven from platinum wire, have an even larger effective surface area and better solution flow compared to platinum sheet electrodes. When measurements require high currents or solution stirring, they can more effectively balance the reactions on the working electrode while maintaining their inertness and stability.

[0024] Furthermore, a wide-band impedance spectroscopy scan was performed by applying a small-amplitude AC perturbation signal at the open-circuit potential. The amplitude of the AC perturbation signal was 5–10 mV. The AC perturbation signal refers to a small-amplitude sinusoidal AC signal superimposed on a DC bias potential (e.g., open-circuit potential) in electrochemical impedance spectroscopy (EIS) measurements. This signal is used to perturb the electrode / electrolyte interface, thereby inducing a corresponding AC response current in the system. Impedance is calculated by measuring the phase difference and amplitude ratio between the voltage and current. The amplitude refers to the peak or effective value of the sinusoidal AC signal. In electrochemical systems, to ensure a linear response, the amplitude of the perturbation signal is usually required to be sufficiently small to avoid changes in the electrode reaction mechanism or significant alterations to the electrode surface state. However, the amplitude cannot be too small, otherwise the signal is easily overwhelmed by noise, leading to decreased measurement accuracy. Therefore, setting the amplitude of the AC perturbation signal in the range of 5 mV to 10 mV aims to provide an optimized condition that ensures both a linear system response and a good signal-to-noise ratio.

[0025] It should be noted that, to ensure the accuracy of the open-circuit potential, the open-circuit potential is defined as the value at which the potential value of the working electrode, after contact with the alkaline electrolyte, fluctuates within ±1 mV for 5 minutes. This stable potential value is a key indicator for determining whether the open-circuit potential has reached a stable state. When the working electrode is immersed in the electrolyte, a series of electrochemical reactions occur on its surface, and the potential gradually stabilizes. Setting "fluctuation within ±1 mV for 5 minutes" as the stabilization standard aims to ensure that the electrode surface reaches a relatively stable quasi-equilibrium state, avoiding measurement errors introduced by potential drift. This stabilization standard balances testing efficiency and result accuracy; too short a time may result in incomplete potential stabilization, while too long a time will reduce detection efficiency. Once the potential of the working electrode meets the above stabilization condition, the measured potential value is confirmed as the open-circuit potential of the nickel mesh substrate under the current electrolyte environment. This stable potential value will serve as the reference potential for subsequent electrochemical impedance spectroscopy scanning, ensuring that the impedance spectroscopy data is acquired under a defined and stable electrochemical condition.

[0026] Furthermore, two characteristic parameters with clear physical meaning were selected from the impedance spectrum as evaluation indicators for polishing quality.

[0027] Firstly, the characteristic frequency corresponding to the maximum phase angle in the mid-frequency range (10Hz–1kHz) is selected as a parameter for evaluating surface roughness. The principle is that for electrode / electrolyte interfaces with rough or porous structures, the charging and discharging behavior of the double layer is no longer equivalent to that of an ideal smooth electrode. The rough structure causes differences in the distribution of interfacial current in the depth direction, resulting in frequency dispersion in the impedance behavior, specifically manifested as a maximum phase angle in the mid-frequency region. Electrochemical theoretical studies have shown a quantitative positive correlation between the characteristic frequency corresponding to this maximum phase angle and the root mean square roughness of the electrode surface—the greater the roughness, the higher the characteristic frequency shifts. Therefore, by detecting the value of this characteristic frequency, the roughness of the nickel mesh surface can be indirectly determined. Based on this principle, this application requires further experimental determination of the preset target frequency band. This target frequency band is not arbitrarily selected, but rather an empirical range derived from statistical analysis of a large amount of experimental data, specifically considering the unique wire diameter and mesh geometry of the twill woven nickel mesh. Its physical significance lies in the fact that the interface frequency response characteristics will only enter this frequency band when the roughness reaches a level sufficient to provide effective mechanical anchoring for subsequent coatings. A frequency below the lower limit of this band indicates insufficient surface roughness, while a frequency above the upper limit indicates over-polishing leading to a smoother surface or the formation of a work-hardened layer.

[0028] Secondly, the ratio Rct / Rs of the charge transfer resistance Rct to the solution resistance Rs is selected as a parameter for evaluating the removal degree of the oxide layer. The charge transfer resistance Rct characterizes the resistance encountered when an electrochemically active substance passes through the electrode / electrolyte interface for charge exchange, and its value is extremely sensitive to the surface state of the electrode. When an oxide layer is present on the surface of the nickel mesh, nickel oxide is a semiconductor or insulating substance, and the energy barrier for electron tunneling or transmission increases significantly, which is manifested as that the Rct value is much higher than that of a clean metal surface; meanwhile, the solution resistance Rs only depends on the conductivity of the electrolyte itself and the geometric structure of the test system, and can be regarded as a constant value when the test conditions are fixed. Therefore, the Rct / Rs ratio can effectively eliminate systematic errors caused by minor differences such as electrode immersion area and electrolyte temperature between different tests, and can sensitively reflect whether the oxide layer has been effectively removed. In the present application, setting Rct / Rs to be not lower than the preset lower limit value is taken as one of the qualification conditions, and this lower limit value can be calibrated by testing the Rct / Rs value of a known qualified sample that has been sufficiently polished under the same conditions. When the ratio is lower than the lower limit value, it indicates that the interfacial charge transfer is hindered and the oxide layer is not completely removed.

[0029] In the present application, the above two parameters are taken as parallel qualification conditions that must be satisfied at the same time, that is, the polishing quality is judged to be qualified only when the characteristic frequency enters the preset target frequency band and the Rct / Rs ratio is not lower than the preset lower limit value, and it is judged to be unqualified if any one of the conditions is not met. The reason for setting the double judgment criteria is that the two parameters respectively correspond to two independent objectives of the polishing process and are irreplaceable to each other: if only the characteristic frequency reaches the standard but Rct / Rs is low, it indicates that the surface roughness has been formed but the residual oxide layer has not been completely removed, and the coating may still peel off due to insufficient interfacial adhesion of the oxide layer; if only Rct / Rs reaches the standard but the characteristic frequency does not enter the target frequency band, it indicates that although the oxide layer has been removed, the roughness is insufficient, and the coating may still have insufficient bonding strength due to the lack of mechanical anchoring. Only when both are satisfied can the polishing quality be comprehensively confirmed to be fully qualified.

[0030] Based on the above detection principle, when the judgment result is unqualified, the polishing process parameters can be adjusted in a targeted manner according to the direction in which the characteristic frequency deviates from the target frequency band and the specific situation where the Rct / Rs ratio deviates from the preset lower limit value. This is because the above two parameters have clear diagnostic directionality: the deviation of the characteristic frequency reflects the problem of geometric morphology, and the low Rct / Rs reflects the problem of interfacial chemical state, both of which provide differentiated feedback information for process adjustment.

[0031] Compared with the prior art, the technical solution of the present application at least has the following beneficial effects: First, the use of electrochemical impedance spectroscopy for detection eliminates the need for complex sample preparation by removing the nickel mesh from the production line, and also eliminates the need for large-scale microscopic observation equipment. This method offers fast detection speed, simple operation, and the potential for online full inspection. Applying electrochemical impedance spectroscopy in reverse to the online detection of the grinding quality of metal substrates requires overcoming the technical obstacle of establishing a correlation between the impedance spectral response and the two physical dimensions of the grinding process (oxide removal and roughening). This application achieves this application extension based on an in-depth analysis of the nature of grinding. Secondly, by simultaneously extracting two physically meaningful parameters, characteristic frequency and impedance ratio, as judgment indicators, a comprehensive evaluation of both the oxide layer removal effect and the roughening effect in grinding quality is achieved, overcoming the limitation of existing methods that can only evaluate one aspect. Using the characteristic frequency falling into a specific target frequency band as one of the judgment conditions avoids the shortcomings of relying solely on impedance amplitude or absolute current density, which is affected by factors such as electrode area and solution resistance, making the judgment standard more robust and reliable. Using the Rct / Rs ratio as another judgment condition can effectively eliminate systematic errors caused by slight differences in electrode immersion area and electrolyte temperature between different tests, and can sensitively reflect whether the oxide layer has been effectively removed. Third, a clear feedback relationship has been established between the test results and the grinding process parameters. Differentiated process adjustments can be made according to the deviation, forming a closed-loop quality control. It is suitable for promotion and application in the production line testing stage and can be adjusted online in real time, which can effectively improve the consistency of nickel mesh grinding quality and product yield.

[0032] In some embodiments described above, this application proposes extracting the maximum phase angle in the 10Hz–1kHz mid-frequency band and its corresponding characteristic frequency from the impedance spectrum as a basis for judging polishing quality. However, in practice, the complexity of the impedance spectrum may lead to uncertainty in the extraction of characteristic frequencies. For example, when multiple maxima appear on the phase angle-frequency curve or when there is no clear maximum peak, accurately and consistently determining the characteristic frequency will directly affect the accuracy and reliability of the polishing quality judgment.

[0033] In response, this application further proposes to extract the maximum value of the phase angle in the mid-frequency band of 10Hz to 1kHz and its corresponding characteristic frequency using the following method: After performing electrochemical impedance spectroscopy (EIS) and recording the impedance spectra, the obtained EIS data is first processed. A continuous phase angle-frequency curve is plotted with the phase angle (usually expressed in degrees or radians) as the ordinate and the logarithm of the frequency (e.g., log(f)) as the abscissa. This curve visually demonstrates the electrochemical response characteristics of the nickel mesh substrate at different frequencies and is an important tool for analyzing its surface state. Subsequently, on this phase angle-frequency curve, all local maxima in the frequency range of 10 Hz to 1 kHz are identified through mathematical analysis or graphical recognition methods. These maxima typically correspond to the characteristic frequency responses of specific electrochemical processes (such as charge transfer, double-layer charging and discharging) at the electrode / electrolyte interface. Once the phase angle maxima are determined, the corresponding frequency value on the abscissa is designated as the characteristic frequency. This characteristic frequency reflects the electrochemical behavior of the nickel mesh substrate surface within a specific frequency range and is closely related to the degree of oxide layer removal and polishing quality indicators such as roughness. Considering the possibility of multiple phase angle maxima in actual testing, to ensure the uniqueness and representativeness of the characteristic frequency, this application stipulates that, within the frequency range of 10 Hz to 1 kHz, the frequency corresponding to the point of maximum phase angle value should be selected as the final characteristic frequency. This helps to focus on the most important electrochemical relaxation process and avoid interference from secondary processes. Furthermore, in some cases, if the polishing quality of the nickel mesh substrate is poor, its electrochemical impedance spectroscopy may not show a clear phase angle maxima peak in the 10 Hz to 1 kHz frequency range. This phenomenon usually indicates an abnormal surface condition of the nickel mesh, such as ineffective removal of the oxide layer or a surface morphology that does not meet requirements. Therefore, this situation is directly judged as unqualified polishing quality to ensure that only nickel mesh substrates that meet the expected electrochemical response can pass the test.

[0034] In some embodiments described above in this application, the polishing quality of nickel mesh substrates is evaluated by scanning and extracting characteristic parameters using electrochemical impedance spectroscopy. However, in practice, accurately and reliably extracting the charge transfer resistance Rct and solution resistance Rs from complex impedance spectra, and then calculating the Rct / Rs ratio, is crucial for ensuring the accuracy and consistency of the detection results.

[0035] In this regard, this application further proposes that the ratio of charge transfer resistance Rct to solution resistance Rs, Rct / Rs, be extracted in the following way: Plotting an Nyquist plot with the real impedance Z′ on the horizontal axis and the imaginary impedance -Z″ on the vertical axis is a common and intuitive method for representing electrochemical impedance spectroscopy data. The Nyquist plot clearly shows the electrochemical process at the electrode / electrolyte interface, where the horizontal axis represents the resistive component of the system and the vertical axis represents the reactive component. This graphical representation facilitates the identification of electrochemical responses in different frequency ranges, providing a foundation for subsequent parameter extraction. Furthermore, the impedance value corresponding to the intersection of the high-frequency arc and the real impedance axis in the Nyquist plot is the solution resistance Rs. The solution resistance Rs mainly reflects the ohmic resistance of the electrolyte itself and the resistance of external circuits such as electrode leads. In the high-frequency region, the capacitive effect at the electrode / electrolyte interface manifests as a short circuit; at this time, the system impedance is mainly determined by the solution resistance. Resistance is the determining factor. Therefore, by identifying the intercept of the high-frequency arc with the real impedance axis, the solution resistance Rs can be accurately obtained. Furthermore, the difference between the impedance value corresponding to the intersection of the low-frequency arc with the real impedance axis in the Nyquist plot and Rs is the charge transfer resistance Rct. The charge transfer resistance Rct is an important parameter for measuring the rate of electrode reaction kinetics, reflecting the ease with which charge transfer occurs at the electrode / electrolyte interface. In the Nyquist plot, the semicircles in the mid-to-low frequency region are usually associated with the charge transfer process. The second intersection of the low-frequency arc with the real impedance axis (or the low-frequency limit) represents the total electrode process resistance, which includes both the solution resistance Rs and the charge transfer resistance Rct. Therefore, by subtracting the determined solution resistance Rs from the total impedance value corresponding to this intersection, the pure charge transfer resistance Rct can be obtained.

[0036] In this example, the method for inspecting the polishing quality of nickel mesh substrates relies on comparing characteristic frequencies with a preset target frequency band. However, if the determination of this preset target frequency band lacks a scientific and quantitative calibration method, its range setting may be subjective or empirical, thereby affecting the accuracy and consistency of polishing quality judgment and making it difficult to effectively compare and standardize the test results between different batches or different operators.

[0037] In response, this application further proposes to define the preset target frequency band through the following steps: The purpose of calibrating the preset target frequency band is to provide an objective and quantitative standard for the quality inspection of nickel mesh substrate grinding. By systematically testing and analyzing the data of nickel mesh samples in different grinding states, the characteristic frequency range reflecting whether the grinding quality is qualified can be scientifically defined, thereby avoiding subjective judgment and improving the reliability and repeatability of the test results.

[0038] During the calibration process, at least three fully polished nickel mesh standard samples and at least three unpolished nickel mesh samples are required. Selecting a sufficient number of samples ensures statistical representativeness and reduces the impact of random errors on the calibration results. The fully polished nickel mesh standard samples represent the ideal polishing state, meaning the surface oxide layer has been completely removed and the surface roughness meets the process requirements. The removal of the surface oxide layer is confirmed using scanning electron microscopy (SEM), and the Ra value is measured using a surface roughness meter to ensure it is within the range of 1.5 μm to 3.0 μm. This ensures that the quality of the standard samples meets high standards and provides a reliable benchmark for subsequent characteristic frequency calibration. The unpolished nickel mesh samples represent the original state before polishing; their surfaces are usually covered with an oxide layer, and the roughness may not meet the requirements. Selecting samples from the same batch ensures the homogeneity of the material itself and eliminates the influence of material differences on the test results. These samples serve as a control group, helping to distinguish the differences in the electrochemical behavior of the nickel mesh before and after polishing.

[0039] Subsequently, each nickel mesh standard sample and the unpolished sample were subjected to electrochemical impedance spectroscopy (EIS) scanning under the same test conditions, and the phase angle-frequency curves of each sample were recorded. Ensuring the consistency of test conditions (such as electrolyte type, concentration, temperature, electrode configuration, AC disturbance signal amplitude, etc.) is crucial for obtaining comparable data. Electrochemical impedance spectroscopy (EIS) scanning can reflect the electrochemical processes at the electrode / electrolyte interface, and the phase angle-frequency curve is a form of EIS data representation. It can intuitively display the capacitance and resistance characteristics of the electrode interface at different frequencies, and is particularly sensitive for identifying changes in surface conditions (such as oxide layer, roughness).

[0040] Based on this, characteristic frequencies corresponding to the maximum phase angle values ​​in the mid-frequency band of 10Hz–1kHz were extracted for each nickel mesh standard sample and unpolished sample, and the arithmetic mean of the characteristic frequencies for both groups of samples was calculated. The maximum phase angle value typically corresponds to the characteristic frequency of the electrochemical reaction or mass transfer process at the electrode / electrolyte interface. By extracting these characteristic frequencies, the electrochemical response of the nickel mesh surface under different polishing conditions can be quantified. Calculating the arithmetic mean helps smooth out fluctuations in individual sample tests, obtaining more representative group characteristic frequencies.

[0041] Finally, the lower limit of the target frequency band is determined by adding one standard deviation to the upper limit of the arithmetic mean of the characteristic frequencies of the unpolished sample group, and the upper limit of the target frequency band is determined by subtracting one standard deviation from the lower limit of the arithmetic mean of the characteristic frequencies of the nickel mesh standard sample group. This method of determining the upper and lower limits of the target frequency band based on statistical methods (arithmetic mean and standard deviation) can scientifically define the characteristic frequency range corresponding to a qualified polishing state. The characteristic frequencies of the unpolished sample group are usually lower, representing a thicker surface oxide layer or poor roughness; the characteristic frequencies of the fully polished nickel mesh standard sample group are usually higher, representing a state of surface oxide layer removal and moderate roughness. By introducing the standard deviation, the natural fluctuations between samples can be taken into account, making the determined target frequency band have a certain degree of tolerance and robustness, ensuring the scientificity and accuracy of the polishing quality qualification judgment.

[0042] In this embodiment, the polishing quality of the nickel mesh substrate can be determined by the ratio of charge transfer resistance Rct to solution resistance Rs (Rct / Rs). However, in practical applications, accurately, objectively, and statistically significantly determining the key threshold for judging whether the polishing quality is acceptable—that is, the preset lower limit of the Rct / Rs ratio—is crucial for ensuring the reliability and consistency of the test results.

[0043] In response, this application further proposes a calibration method for a preset lower limit value, which specifically includes the following steps: First, at least three well-polished nickel mesh standard samples were selected. These well-polished nickel mesh standard samples underwent rigorous screening and verification, and their surface oxide layer was effectively removed. Specifically, these samples were polished under the same conditions, and visual inspection confirmed that the surface exhibited a uniform silvery-white metallic luster, while scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) confirmed that the surface oxygen atomic percentage was less than 1%. This dual verification mechanism ensured that the polishing quality of the selected standard samples reached an ideal state, i.e., the surface oxide layer was completely removed, providing a reliable benchmark for subsequent parameter calibration.

[0044] Next, each of the aforementioned nickel mesh standard samples was tested under electrochemical impedance spectroscopy (EIS) scanning conditions. These testing conditions were consistent with those used in actual testing to ensure the validity and comparability of the calibration results. Through EIS scanning, the impedance spectra of each standard sample could be obtained, and the ratio of its charge transfer resistance Rct to solution resistance Rs, Rct / Rs, could then be extracted.

[0045] Subsequently, the Rct / Rs values ​​of each nickel mesh standard sample were calculated, and the arithmetic mean of these values ​​was taken. Since there may be some batch differences or operational fluctuations in the preparation and polishing process of the nickel mesh substrate, using multiple standard samples for testing and calculating the average value can effectively reduce the randomness of the test results of a single sample and improve the representativeness of the calibration results.

[0046] Finally, the value obtained by subtracting three standard deviations from the arithmetic mean is used as the preset lower limit. This method, based on statistical principles, considers the inherent variability between samples. By subtracting three standard deviations from the mean, a relatively conservative and highly confident lower limit can be set. This means that only when the Rct / Rs ratio of the nickel mesh substrate under test is higher than this preset lower limit can it be judged as having passed the polishing quality test. This ensures that the oxide layer on the surface of the nickel mesh has been fully removed after polishing, avoiding quality problems caused by residual oxide layers.

[0047] Specifically, this application further proposes a specific method for adjusting grinding process parameters, including: increasing the grinding mesh number of quartz sand when the characteristic frequency is in a preset target frequency band; decreasing the grinding mesh number of quartz sand when the characteristic frequency is higher than the preset target frequency band; maintaining the current grinding mesh number of quartz sand when the characteristic frequency falls into the preset target frequency band but the Rct / Rs ratio is lower than the preset lower limit value; and extending the grinding time and adding a surface cleaning process after grinding.

[0048] This adjustment step aims to purposefully adjust key parameters during the grinding process based on the actual grinding quality test results of the nickel mesh substrate, ensuring that the surface condition of the nickel mesh substrate meets the expected quality requirements. Specifically, when the characteristic frequency is lower than the preset target frequency band, this usually indicates that the nickel mesh substrate is not sufficiently ground, possibly due to incomplete oxide layer removal or insufficient surface activity. In this case, the abrasive mesh size should be increased, i.e., finer quartz sand particles should be used for grinding. Finer abrasive provides a more refined grinding action, helping to more thoroughly remove residual oxide layers from the surface of the nickel mesh substrate and form a more uniform and active surface morphology, thereby shifting the characteristic frequency towards the preset target frequency band.

[0049] When the characteristic frequency is higher than the preset target frequency band, it may indicate that the nickel mesh substrate surface is over-polished, has excessively high surface roughness, or is in an overly active and unstable state. To adjust the characteristic frequency back to the preset target frequency band, the grit size of the silica sand needs to be reduced, i.e., coarser silica sand particles should be used. By using coarser abrasive, the surface of the nickel mesh substrate can be appropriately adjusted, for example, by creating specific surface textures or reducing overactive surface conditions, thereby lowering the characteristic frequency to the target range and achieving an ideal surface condition.

[0050] When the characteristic frequency is within the preset target frequency range, it indicates that the surface morphology and roughness of the nickel mesh substrate have basically met the requirements. However, if the ratio of charge transfer resistance Rct to solution resistance Rs, Rct / Rs, is still lower than the preset lower limit, this usually means that there may still be trace amounts of residual oxides, adsorbed impurities, or contaminants generated during the polishing process on the surface of the nickel mesh substrate. These substances will hinder the effective transfer of charge. In this case, maintain the current quartz sand grit to preserve the achieved surface morphology. At the same time, extending the polishing time can further ensure that the residual oxide layer is completely removed. In addition, adding a surface cleaning process after polishing, such as using ultrasonic cleaning or solvent cleaning, can effectively remove tiny particles, oil, or other contaminants from the surface of the nickel mesh substrate, thereby reducing charge transfer resistance, increasing the Rct / Rs ratio to reach or exceed the preset lower limit, and ensuring that the surface of the nickel mesh substrate has excellent electrochemical performance.

[0051] To further illustrate the technical solution of this application, a specific embodiment is provided for description; Hydrolysis electrodes (such as those used for hydrogen production via water electrolysis) typically use a nickel mesh as a conductive substrate. A catalytic functional coating is formed on its surface through methods such as plasma spraying. The bonding strength between the coating and the nickel mesh substrate directly determines the electrode's service life and catalytic performance stability. Before the spraying process, the nickel mesh substrate must undergo a pre-treatment process of grinding to remove the surface oxide layer and create an appropriate roughness, thereby providing a good mechanical anchoring interface for the subsequent coating. Whether the grinding quality meets the standards directly affects the coating's bonding strength, density, and long-term service stability, making it a critical quality control point in the manufacturing process of hydrolysis electrodes. Therefore, the method described in this application is used to monitor the grinding quality of the nickel mesh substrate.

[0052] First, before formally applying this method, the key parameters of the detection system need to be calibrated. Technicians calibrated the target frequency band and preset lower limit values ​​according to pre-defined procedures. They selected at least three fully polished nickel mesh standard samples and at least three unpolished nickel mesh samples. The fully polished nickel mesh standard samples were confirmed by scanning electron microscopy to have their surface oxide layer removed, and their surface roughness Ra reached 1.5 μm to 3.0 μm. The unpolished nickel mesh samples were twill-woven nickel meshes from the same batch that had not undergone any polishing treatment. These samples were immersed in a 1 mol / L potassium hydroxide aqueous solution, using the sample as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet electrode as the counter electrode, forming a three-electrode detection system. At the open-circuit potential of the nickel mesh substrate (the open-circuit potential is determined by placing the three electrodes in the electrolyte and waiting for the working electrode to come into contact with the alkaline electrolyte, and the potential value fluctuates by no more than ±1mV within 5 minutes, and is taken as the stable potential value), an AC perturbation signal with an amplitude of 5mV was applied through an electrochemical workstation, and electrochemical impedance spectroscopy was scanned in the frequency range of 10mHz to 100kHz, and the phase angle-frequency curve of each sample was recorded.

[0053] Subsequently, technicians extracted the characteristic frequency values ​​corresponding to the maximum phase angles of each nickel mesh standard sample and the unpolished sample in the mid-frequency band of 10Hz to 1kHz, and calculated the arithmetic mean of the characteristic frequencies for both groups of samples. For example, the arithmetic mean of the characteristic frequencies of the unpolished sample group was 40Hz with a standard deviation of 5Hz; the arithmetic mean of the characteristic frequencies of the nickel mesh standard sample group was 600Hz with a standard deviation of 10Hz. According to the calibration rules, the upper limit of the arithmetic mean of the characteristic frequencies of the unpolished sample group (40Hz) plus one standard deviation (5Hz) was used as the lower limit of the target frequency band (45Hz), and the upper limit of the target frequency band (590Hz) was used as the lower limit of the arithmetic mean of the characteristic frequencies of the nickel mesh standard sample group (600Hz) minus one standard deviation (10Hz). Thus, the target frequency band of 50Hz to 500Hz was determined.

[0054] To calibrate the preset lower limit, technicians selected at least three well-polished nickel mesh standard samples. These samples, visually inspected, exhibited a uniform silvery-white metallic luster, and scanning electron microscopy (SEM) analysis confirmed that the surface oxygen atomic percentage was less than 1%. These samples were tested under the same electrochemical impedance spectroscopy (EIS) scanning conditions, and the ratio of charge transfer resistance (Rct) to solution resistance (Rs) for each nickel mesh standard sample, Rct / Rs, was calculated. For example, the arithmetic mean of the calculated Rct / Rs values ​​was 100, and the standard deviation was 5. The preset lower limit was calculated by subtracting three times the standard deviation from the arithmetic mean (100 - 3 x 5 = 85).

[0055] After parameter calibration, this method was applied to the quality inspection of nickel mesh substrate grinding on the production line. Once a batch of twill-woven nickel mesh substrates was ground, it was immediately immersed in a 1 mol / L potassium hydroxide aqueous solution. Using the nickel mesh substrate as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet electrode as the counter electrode, a three-electrode detection system was formed. At the open-circuit potential of the nickel mesh substrate, an AC perturbation signal with an amplitude of 5 mV was applied to the working electrode via an electrochemical workstation. Electrochemical impedance spectroscopy was performed in the frequency range of 10 mHz to 100 kHz, and the impedance spectra were recorded.

[0056] Subsequently, the system automatically extracts characteristic parameters from the impedance spectrum. First, it plots a phase angle-frequency curve with the phase angle as the vertical axis and the logarithm of the frequency as the horizontal axis. The system identifies the maximum phase angle point within the 10Hz–1kHz frequency range and uses the frequency corresponding to this maximum as the characteristic frequency. For example, if multiple phase angle maxima exist within the 10Hz–1kHz range, the system selects the frequency corresponding to the largest maximum as the characteristic frequency. If no clear phase angle maximum peak appears, the grinding quality is directly deemed unqualified. Simultaneously, the system plots a Nyquist diagram with the real impedance Z′ as the horizontal axis and the imaginary impedance -Z″ as the vertical axis. The impedance value corresponding to the intersection of the high-frequency arc and the real impedance axis in the Nyquist diagram is the solution resistance Rs. The difference between the impedance value corresponding to the intersection of the low-frequency arc and the real impedance axis in the Nyquist diagram and Rs is the charge transfer resistance Rct, and the Rct / Rs ratio is then calculated.

[0057] Reference Figure 2 and Figure 3 As shown, when monitoring a certain nickel mesh substrate, its characteristic frequency was 695.4 Hz, and the Rct / Rs ratio was approximately 110. According to the preset judgment criteria, the target frequency band is 50 Hz to 500 Hz, with a preset lower limit of 85. Since the characteristic frequency of this batch of nickel mesh substrates (695.4 Hz) is higher than the upper limit of the target frequency band (500 Hz), the grinding quality is deemed unqualified. Based on the deviation of the characteristic frequency above 500 Hz, the system prompts the operator to reduce the grit of the quartz sand to avoid over-grinding or excessively high surface roughness.

[0058] This method enables rapid, quantitative, and online detection of the grinding quality of nickel mesh substrates. Compared to traditional offline detection methods, it eliminates the need for complex sample preparation, provides real-time feedback of results, and significantly improves production efficiency and product quality control. Furthermore, by comprehensively evaluating characteristic frequencies and the Rct / Rs ratio, the system can more comprehensively assess the degree of oxide layer removal and microstructure on the nickel mesh surface, providing a reliable substrate for subsequent processes. When the detection results are unsatisfactory, the system can provide targeted adjustments to grinding process parameters based on the specific deviation, allowing for timely detection and correction of problems during production and preventing subsequent product defects caused by substandard grinding quality.

[0059] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for inspecting the polishing quality of a nickel mesh substrate, wherein the nickel mesh substrate is a twill-woven nickel mesh, characterized in that, Includes the following steps: The polished nickel mesh substrate is immersed in an alkaline electrolyte, and the nickel mesh substrate is used as the working electrode, together with the reference electrode and the counter electrode, to form a three-electrode detection system. An AC perturbation signal was applied to the working electrode using an electrochemical workstation, and an electrochemical impedance spectroscopy scan was performed in the frequency range of 10 mHz to 100 kHz. The impedance spectrum was recorded. The electrochemical impedance spectroscopy scan was performed at the open circuit potential of the nickel mesh substrate. The following characteristic parameters are extracted from the impedance spectrum: the maximum value of the phase angle in the mid-frequency band of 10Hz to 1kHz and its corresponding characteristic frequency, and the ratio of charge transfer resistance Rct to solution resistance Rs, Rct / Rs. When the characteristic frequency enters the preset target frequency band and the Rct / Rs ratio is not lower than the preset lower limit, the polishing quality is deemed to be qualified; otherwise, the polishing quality is deemed to be unqualified. The preset target frequency band is the characteristic frequency range that indicates that the surface roughness of the nickel mesh after polishing has reached the required level. The preset lower limit is the critical Rct / Rs value that indicates that the oxide layer on the surface of the nickel mesh has been removed after polishing. When the grinding quality is deemed unqualified, the grinding process parameters are adjusted based on the deviation of the characteristic frequency from the preset target frequency band and the deviation of the Rct / Rs ratio from the preset lower limit.

2. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: The alkaline electrolyte is an aqueous solution of potassium hydroxide, and the concentration of the aqueous solution of potassium hydroxide is 0.5 mol / L to 6 mol / L.

3. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: The reference electrode is a saturated calomel electrode or a silver / silver chloride electrode, and the counter electrode is a platinum sheet electrode or a platinum mesh electrode.

4. The method for detecting the polishing quality of the nickel mesh substrate according to claim 1, characterized in that: The amplitude of the AC disturbance signal is 5–10 mV.

5. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: The open circuit potential is determined as follows: the working electrode, reference electrode and counter electrode in the three-electrode detection system are placed in an alkaline electrolyte. When the potential value of the working electrode after contact with the alkaline electrolyte does not fluctuate by more than ±1mV within 5 minutes, the stable potential value is taken as the open circuit potential.

6. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: The maximum value of the phase angle in the mid-frequency band of 10Hz to 1kHz and its corresponding characteristic frequency are extracted in the following way: Plot the phase angle-frequency curve with the phase angle as the vertical axis and the logarithm of the frequency as the horizontal axis from the impedance spectrum. Determine the maximum point of the phase angle in the frequency range of 10Hz to 1kHz, and use the frequency value corresponding to the maximum point as the characteristic frequency. Specifically: if multiple phase angle maxima exist within the frequency range of 10Hz to 1kHz, the frequency value corresponding to the largest maximum value is selected as the characteristic frequency; if no clear phase angle maxima peak appears within the frequency range of 10Hz to 1kHz, the polishing quality of the nickel mesh substrate is deemed unqualified.

7. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: The ratio of charge transfer resistance Rct to solution resistance Rs, Rct / Rs, is extracted as follows: Plot the Nyquist plot with the real impedance Z′ on the horizontal axis and the imaginary impedance -Z″ on the vertical axis. The impedance value corresponding to the intersection of the high-frequency arc and the real impedance axis in the Nyquist plot is the solution resistance Rs. The difference between the impedance value corresponding to the intersection of the low-frequency arc and the real impedance axis in the Nyquist plot and Rs is the charge transfer resistance Rct.

8. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: The preset target frequency band is calibrated through the following steps: Take at least three fully polished nickel mesh standard samples and at least three unpolished nickel mesh samples. The fully polished nickel mesh standard samples are nickel meshes whose surface oxide layer has been removed and whose surface roughness Ra reaches 1.5μm to 3.0μm as confirmed by scanning electron microscopy. The unpolished nickel mesh samples are twill woven nickel meshes from the same batch that have not undergone any polishing treatment. Electrochemical impedance spectroscopy was performed on each nickel mesh standard sample and the unpolished sample under the same test conditions, and the phase angle-frequency curves of each sample were recorded. The characteristic frequency values ​​corresponding to the maximum values ​​of the phase angles of each nickel mesh standard sample and the unpolished sample in the mid-frequency band of 10Hz to 1kHz were extracted respectively, and the arithmetic mean of the characteristic frequencies of the two groups of samples was calculated respectively. The lower limit of the target frequency band is determined by adding one standard deviation to the upper limit of the arithmetic mean of the characteristic frequencies of the unpolished sample group, and the upper limit of the target frequency band is determined by subtracting one standard deviation from the lower limit of the arithmetic mean of the characteristic frequencies of the nickel mesh standard sample group.

9. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: The preset lower limit value is calibrated through the following steps: Take at least three fully polished nickel mesh standard samples. The fully polished nickel mesh standard samples are nickel meshes that, under the same polishing conditions, have a uniform silvery-white metallic luster when visually inspected and have a surface oxygen atomic percentage of less than 1% confirmed by scanning electron microscopy energy dispersive spectroscopy analysis. Each nickel mesh standard sample was tested under electrochemical impedance spectroscopy scanning conditions. The Rct / Rs value of each nickel mesh standard sample was calculated and the arithmetic mean was taken. The value obtained by subtracting three times the standard deviation from the arithmetic mean was used as the preset lower limit value.

10. The method for detecting the polishing quality of a nickel mesh substrate according to claim 1, characterized in that: Adjusting the polishing process parameters includes: When the characteristic frequency is lower than the preset target frequency band, increase the grinding mesh of the quartz sand; When the characteristic frequency is higher than the preset target frequency band, reduce the grinding mesh of the quartz sand; When the characteristic frequency falls into the preset target frequency band, but the Rct / Rs ratio is lower than the preset lower limit, the current quartz sand grinding mesh is maintained. The grinding time is extended, and a surface cleaning process is added after grinding.

Citation Information

Patent Citations

  • Picoampere-level precision data acquisition method and system of special large model for corrosion industry

    CN120801469A

  • Surface finish quality evaluation system and method

    US20200269439A1